Correlation Between the Glasgow Blatchford score and Outcomes of Acute Upper Gastrointestinal Bleeding in Phetchabun Hospital - Chantharakhit, Chaichana (Journal of Health Science of Thailand, 2017)
The Glasgow Blatchford score can be used to classify patients with upper gastrointestinal bleeding as low risk or high risk for appropriate management. The objective of this study was to assess the relation between the Glasgow Blatchford score and outcomes of upper gastrointestinal bleeding in Phetchabun hospital. Data were collected from medical records of patients with upper gastrointestinal bleeding in medical ward and surgical ward between January to December 2010. Risk scores were calculated and used to classify patients. The Glasgow Blatchford score and outcomes of upper gastrointestinal bleeding such as re-bleeding, upper gastrointestinal endoscopy or surgical intervention and death showed significant positive linear relationship (p<0.0r). In this study Blatchford score greater than 6 could be used to identify high risk patients; and the proportion of patients requiring endoscopy or surgical intervention was significantly higher in the high risk group (p<0.05). Thus, the Glasgow Blatchford score could be a useful tool to categorize patients as high risk and low risk in order to provide appropriate medical services to individual patients in Phetchabun hospital.